2022
DOI: 10.3390/genes13122332
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Role of CUB and Sushi Multiple Domains 1 (CSMD1) in Human Diseases

Abstract: CUB and Sushi Multiple Domains 1 (CSMD1), a tumour suppressor gene, encodes a large membrane-bound protein including a single transmembrane domain. This transmembrane region has a potential tyrosine phosphorylation site, suggesting that CSMD1 is involved in controlling cellular functions. Although the specific mechanisms of action for CSMD1 have not yet been uncovered, it has been linked to a number of processes including development, complement control, neurodevelopment, and cancer progression. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Gliomas are aggressive brain tumors that present significant challenges in treatment and prognosis despite advances in therapeutic strategies. The tumor suppressor role of CSMD1 has been demonstrated in several cancers [ 33 ] but its role in glioma has not been determined. In this study, we first revealed that elevating CSMD1 expression in glioma cell lines significantly suppressed crucial malignant traits including cancer cell proliferation, migration, invasion, and the properties linked with the cancer stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas are aggressive brain tumors that present significant challenges in treatment and prognosis despite advances in therapeutic strategies. The tumor suppressor role of CSMD1 has been demonstrated in several cancers [ 33 ] but its role in glioma has not been determined. In this study, we first revealed that elevating CSMD1 expression in glioma cell lines significantly suppressed crucial malignant traits including cancer cell proliferation, migration, invasion, and the properties linked with the cancer stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Despite CR1 being mainly expressed in erythrocytes, B cells, macrophages, and granulocytes ( Khera and Das, 2009 ), the new type 1 complement receptor CSMD1 was found to be highly expressed in the CNS and epithelial cells ( Kraus et al, 2006 ). CSMD family consists of CSMD1, CSMD2, and CSMD3 members, and CSMD1 is the most well-studied member ( Ermis Akyuz and Bell, 2022 ). Similar to CR1, CSMD1 was shown to bind C4b and C3b to promote their degradation by Factor I ( Escudero-Esparza et al, 2013 ), and it is highly expressed in the CNS in 80% of GABAR-positive synapses and 40% of NMDAR-positive synapses ( Baum et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CSMD1 and CSMD2 polymorphisms were associated with SZ ( Håvik et al, 2011 ; Rose et al, 2013 ), while CSMD3 was associated with both SZ and ASD ( Mizukami et al, 2016 ). It was shown that CSMD1 could bind and inhibit RTKs such as EGFR (potent inducer of IEGs) and CSMD1 can also modulate TGFβ receptor signaling ( Gialeli et al, 2021 ; Ermis Akyuz and Bell, 2022 ). Although both EGFR and TGFβRs are expressed in the CNS ( Dobolyi et al, 2012 ; Romano and Bucci, 2020 ), neuronal cells have other important RTKs such as TrkA and TrkB neurotrophic receptors, that bind BDNF and NGF, respectively ( Haddad et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSMD1 encodes the CUB and Sushi multiple domains 1 protein, a transmembrane protein that controls several cellular functions. CSMD1 has been linked to several diseases, such as cancer, Parkinson's disease, and schizophrenia [41], indicating that CSMD1 dysfunction has various clinical effects. Several genetic studies reported that CSMD1 was associated with schizophrenia [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%